Pengaruh Bahan Pencucian Pulp pada Biji dan Lama Perendaman Benih dalam Air Kelapa Muda terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Silsri Kardena; Helti Andraini; Frederika Eliesti (Eduscience Development Journal, 2021)
Research on the Effect of Pulp Washing on Seeds and Duration of Soaking Seeds in Young Coconut Water on the Growth of Cacao Seeds (Theobroma cacao L.), has been carried out in Jorong Panta Nagari Koto Gadang Koto Anau Lembang Jaya District Solok Regency with an altitude of ±1000 Mdpl. This study aimed to obtain the best results on the growth of cacao seedlings and to obtain the interaction of pulp washing material and the duration of immersion of seeds in young coconut water on the growth of cacao seedlings. The method used was Factorial Randomized Block Design (RAKF) for factor I washing the pulp of the seeds, namely P1=Rub ash and P2=Sawdust. Faktor II immersion time of coconut water W0=Without soaking, W1=3, W2=5, W3=7, W4=9. Parameters observed were seed germination (%), germination rate (days), plant height (cm), number of leaves (strands), leaf width (cm), leaf length (cm), stem diameter (mm), root length primary (cm). the result showed that different pulp washing materials showed a significant effect on leaf width and primary root length. The duration of soaking the seeds in different young coconut water also showed a significanteffect on plant height and leaf width and there was a significant interaction on leaf width and leaf length. The best treatment was found in the ash washing material and the best seed soaking time was 7 hours